Buprenorphine Maintenance Subjects Are Hyperalgesic and Have No Antinociceptive Response to a Very High Morphine Dose - Athanasos, Peter; Ling, Walter; Bochner, Felix; White, Jason M; Somogyi, Andrew A (Pain medicine (Malden, Mass.), 2019)
Abstract Objective Acute pain management in opioid-dependent persons is complicated because of tolerance and opioid-induced hyperalgesia. Very high doses of morphine are ineffective in overcoming opioid-induced hyperalgesia and providing antinociception to methadone-maintained patients in an experimental setting. Whether the same occurs in buprenorphine-maintained subjects is unknown. Design Randomized double-blind placebo-controlled. Subjects were tested on two occasions, at least five days apart, once with intravenous morphine and once with intravenous saline. Subjects were tested at about the time of putative trough plasma buprenorphine concentrations. Setting Ambulatory. Subjects Twelve buprenorphine-maintained subjects: once daily sublingual dose (range = 2–22 mg); no dose change for 1.5–12 months. Ten healthy controls. Methods Intravenous morphine bolus and infusions administered over two hours to achieve two separate pseudo-steady-state plasma concentrations one hour apart. Pain tolerance was assessed by application of nociceptive stimuli (cold pressor [seconds] and electrical stimulation [volts]). Ten blood samples were collected for assay of plasma morphine, buprenorphine, and norbuprenorphine concentrations until three hours after the end of the last infusion; pain tolerance and respiration rate were measured to coincide with blood sampling times. Results Cold pressor responses (seconds): baseline: control 34 ± 6 vs buprenorphine 17 ± 2 (P = 0.009); morphine infusion-end: control 52 ± 11(P = 0.04), buprenorphine 17 ± 2 (P > 0.5); electrical stimulation responses (volts): baseline: control 65 ± 6 vs buprenorphine 53 ± 5 (P = 0.13); infusion-end: control 74 ± 5 (P = 0.007), buprenorphine 53 ± 5 (P > 0.98). Respiratory rate (breaths per minute): baseline: control 17 vs buprenorphine 14 (P = 0.03); infusion-end: control 15 (P = 0.09), buprenorphine 12 (P < 0.01). Infusion-end plasma morphine concentrations (ng/mL): control 23 ± 1, buprenorphine 136 ± 10. Conclusions Buprenorphine subjects, compared with controls, were hyperalgesic (cold pressor test), did not experience antinociception, despite high plasma morphine concentrations, and experienced respiratory depression. Clinical implications are discussed.